Talking Back in Defense of Defending DEI and the Politics of Inclusion - Nicole A. Cooke (The Political Librarian, 2025)
“Talking back,” as scholar bell hooks reminds us, is never just about oral, verbal, and written speech—it is an act of resistance, a transformation of silence into language and action. It is how marginalized communities reclaim and reprioritize their right to think, to speak, to define the world on their own terms. Similarly, activist, writer, and librarian Audre Lorde’s “The Uses of Anger” teaches us that anger—particularly the righteous anger born of injustice and inequity—is not destructive, but can be clarifying and transformative. Lorde said that anger is “loaded with information and energy,” it is a dynamic force that can illuminate generational systems of oppression and domination, and fuel the collective work of liberation. This special issue of The Political Librarian, Defending DEI and the Politics of Inclusion, stands firmly on this foundation of righteous anger and talking back. The call for proposals recognized the urgency of this political moment: “Diversity, Equity, and Inclusion (DEI) initiatives are facing coordinated political attacks at every level of government,” while “neutrality” and “privacy” are being weaponized to suppress equity work and dismantle progress. With this tense and tenuous political and societal climate in mind, the articles and short essays gathered here rebuke silence. They talk back, they bear witness, and they build.
Keywords: Diversity; Equity; Inclusion; resistance; talking back